Carotid Intima-Media Thickness in 100 Iraqi Patients with Hand Osteoarthritis - Al-Rawi, Ziad S.; Gorial, Faiq I.; Hafed, Kahtan A.; Hashim, Thikra N. (Journal of the Faculty of Medicine Baghdad, 2011)
Background: Hand osteoarthritis (HOA) is a common joint disorder leading to considerable pain and with substantial impact on hand function. Carotid intima-media thickness (CIMT) is a measurable index of the presence of atherosclerosis. Increased CIMT is associated with increased cardiovascular mortality and morbidity, so early diagnosis and management may improve quality of life. Objective: To assess the relationship between carotid intima-media thickness (CIMT) and hand osteoarthritis (HOA), and to evaluate the predictors of this relationship.Patients and Methods: One hundred Iraqi HOA patients and 100 healthy controls were included in this study. Full history was taken and complete clinical examination was done for all patients. Disease characteristics [age, sex, duration, body mass index (BMI), waist circumference, family history of HOA, smoking history, lipid lowering agent use] were also documented. Laboratory analysis included complete blood count, erythrocyte sedimentation rate (ESR), C-reactive protein (CRP), and lipid profile. Individuals in both groups were assessed for CIMT by B-mode ultrasonography. X-rays of both hands was taken for patients and was graded according Kellgrenand Lawrence scale.Results: Fifty five (55%) Iraqi HOA patients have increased CIMT compared with 38 % of controls (p=0.02). There was no statistical significant association between increased CIMT and HOA radiographical grading (p=0.72). The lipid profile was the only predictor of increased CIMT in patients with HOA [p=0.02, OR (95% CI) = 3.24 (1.20-8.75)] Conclusions: There is increased frequency of increased CIMT (55%) in Iraqi patients with HOA. Abnormal lipid profile is the only significant predictor of increased CIMT.